PENGARUH PROFITABILITAS DAN LEVERAGE TERHADAP AGRESIVITAS PAJAK PERUSAHAAN FARMASI DI BEI 2020–2024 - Halimah, Cici; Sembiring, Masta (UNIVERSITAS DHARMAWANGSA, 2025)
This study is motivated by indications of tax aggressiveness practices among pharmaceutical sub-sector companies listed on the Indonesia Stock Exchange (IDX). Such practices raise concerns about corporate tax compliance and the transparency of financial reporting. To examine the factors influencing tax aggressiveness, this study employs a quantitative approach using panel data regression analysis. The independent variables include profitability and leverage, while the dependent variable is tax aggressiveness. The sample was selected using a purposive sampling method from pharmaceutical companies that met the criteria during the 2020–2024 period, with secondary data obtained from the official IDX website. Data analysis was conducted using E-Views 12 software. The results show that profitability and leverage have no significant effect on tax aggressiveness, either partially or simultaneously. The coefficient of determination (R²) of 0.0216 indicates that both variables explain only 2.16% of the variation in tax aggressiveness. These findings imply that other factors beyond profitability and leverage play a more dominant role in determining the level of tax aggressiveness among pharmaceutical companies in Indonesia